Bygningskapital og Bygningsomkostninger. Foredrag, den 14. - 16. Oktober 1940. - Ridder, Johs. (Tidsskrift for Landøkonomi, 2018)
Bygningskapital og Bygningsomkostninger. Foredrag, den 14. - 16. Oktober 1940.